2012
DOI: 10.1002/ejlt.201200115
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy for analysis of oil content and fatty acid profile in almond flour

Abstract: Almond kernels show large variability for oil content and fatty acid profile. The objective of this research was to evaluate the potential of near infrared (NIR) reflectance spectroscopy (NIRS) for the analysis of these traits in almond flour. Ground kernels of 181 accessions collected in 2009 were used for developing calibration equations for oil content and concentrations of individual fatty acids. Calibration equations were developed using second derivative transformation and modified partial least squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Recently, NIRS has also been applied to the characterization of fatty acids in meat and food power samples [ 23 , 24 , 25 , 26 , 27 ]. But the models developed in these reports need improvements for better prediction of some fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, NIRS has also been applied to the characterization of fatty acids in meat and food power samples [ 23 , 24 , 25 , 26 , 27 ]. But the models developed in these reports need improvements for better prediction of some fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…But the models developed in these reports need improvements for better prediction of some fatty acids. For example, in the study of Fernandez-Cuesta et al [ 24 ], only C18:1 and C18:2 showed good prediction, with R 2 being 0.97 and 0.98, and RPD being 5.37 and 7.35, respectively; in contrast, the prediction performance for C16:0 ( R 2 = 0.54, RPD = 1.41) and C18:0 ( R 2 = 0.51, RPD = 1.44) was far less acceptable. Fatty acids varying in chain length and unsaturation level possess different near-infrared spectra [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sunflower genotypes in traditional and mutant groups must be identified using combined discriminant analytical methods and NIRS to discriminate the profile of FAs. Fernandez-Cuesta et al [72] confirmed that NIRS can be applied for accurate high-throughput analysis of oil content and concentrations of oleic and linoleic acids in almond samples. NIRS discrimination of different traits mainly depended at wavelengths of 2304 and 2344 nm in the spectral regions from 2240 to 2380 nm.…”
Section: Near-infrared Spectroscopymentioning
confidence: 97%
“…Fernandez‐Cuesta et al. confirmed that NIRS can be applied for accurate high‐throughput analysis of oil content and concentrations of oleic and linoleic acids in almond samples. NIRS discrimination of different traits mainly depended at wavelengths of 2304 and 2344 nm in the spectral regions from 2240 to 2380 nm.…”
Section: Near‐infrared Spectroscopymentioning
confidence: 99%